SISTEM INFORMASI FRONT OFFICE UNTUK PENINGKATAN PELAYANAN PELANGGAN DALAM RESERVASI KAMAR HOTEL - Victor Marudut Mulia Siregar; Nancy Florida Siagian (Politeknik Bisnis Indonesia, 2021)
The research aims to overcome the problem of managing customer data, room data, and transaction data manually at Hotel Fergael. The management of customer data, room data and transaction data that are processed manually, is overcome by building a Front Office Information System for hotel room reservations at Hotel Fergael. The results of the Front Office Information System research for hotel room reservations at the Fergael Hotel can be done quickly, effectively and efficiently at the receptionist's work time, making reports can also assist managers in seeing reservations that have or have occurred at the Fergael Hotel. The system is designed in the form of Visual Basic and uses a MySQL database. With this research, the receptionist can expedite the activities that run at the Fergael Hotel, especially room input, customer input, and room reservations that occur at the Fergael Hotel Pematangsiantar.